Selection of dual-channel supply chain cooperation mode of older adults care service under the government subsidy strategy - Tong Zhao; Qiaoming Hou (PLoS ONE, 2025)
This study develops a dual-channel supply chain coordination model for services aimed at older adults, taking into account differentiated government subsidies. Utilizing Hotelling and Stackelberg game models, we systematically examine optimal strategies across three distinct scenarios: a non-cooperative mode, cooperation between online channels and logistics suppliers, and a tripartite collaboration involving both online and offline channels alongside logistics suppliers. The results demonstrate that the optimal pricing and service levels attained in cooperative scenarios exceed those observed in non-cooperative settings. Furthermore, within the framework of tripartite collaboration, the influence of enhanced service levels on the optimization of both service pricing and quality is particularly significant. It is noteworthy that government subsidies tend to exert a marginally greater incentive effect on offline service channels compared to online ones, thereby increasing the focus on addressing the emotional needs of older adults. Overall, this research represents a pioneering effort to compare these three service cooperation models, leveraging government subsidies as a catalyst. It not only enhances the advantages of differentiated dual-channel services but also promotes the efficient allocation of resources in elder care through the identification of suitable collaborative strategies.